Layering Public Park Histories: Uncovering the Effects of Restoration Idea[l]s in Post-War Urban Spaces in Germany and the U.S. - Laura Brannan Fretwell; Eliane Schmid (European Journal of Geography)
This paper proposes a lens of analysis for studying how public urban park creation, often presented as inherently beneficial for the public by planners, government officials, and stakeholders, served to enforce prevailing social and political norms by excluding unwanted visitors and fostering specific codes of conduct. The two case studies of post-war park development in Richmond, Virginia, U.S., and Hamburg, DE, exemplify the social and political effects of restoration ideas and ideals on beneficiaries and non-beneficiaries. In Richmond, the construction of Chimborazo Park displaced and excluded an African American (Black) community during the aftermath of the Civil War, while Hamburg's Alsterpark was created within the city’s general post-World War II greening initiatives that included forced expropriation and behavior regulation. The joint spatial humanities based approach, which includes GIS modeling and archival source analysis, furthers historical investigation to more deeply understand patterns of displacement, exclusion, and social control. The paper offers an approach for critically examining the planning histories of parks that were created under the justification of restoration but operated as sites of contestation and ideology during moments of societal, political, and social reform.